Kitab Suci dan Kegiatan Ekonomi: Perspektif Kitab-kitab Kebijaksanaan - Adi, Suwarto (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2020)
This paper aims at elucidating the meaning of economic works from the Scripture, the Christian Bible’s Wisdom Books. Making use of the hermeneutics approach, more particular of Gadamer’s theoretical framework, this paper is to dialogue the meaning of economic works in the past with the modern’s perspective of works. Eventually, there had been a similarity between both meanings of works biblical-based and modern one i.e. if human being wants to be wealthy and meaningful person, in the theological perspective, should make it harmony between a hard and diligent works with the tenets of faith to God. It is based on such an idea, the church could and enabled to develop a theology or ethics of works particularly in the field of economic.